PENGARUH ACCOUNT RECEIVABLE TURNOVER, DEBT TO ASSET RATIO, DAN DIVIDEND PAYOUT RATIO TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN ANEKA INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2020 - Naomi Febrianti Siringoringo; Arthur Simanjuntak; Rike Yolanda Panjaitan; Melanthon Rumapea (JURNAL MANAJEMEN, 2022)
This study aims to determine the effect of Account Receivable Turnover, Debt to Asset Ratio, and Dividend Pay-out Ratio on Profit Growth in Various Industrial Companies Listed on the Indonesia Stock Exchange in the 2016-2017 period. This study uses secondary data that can be accessed through the Indonesia Stock Exchange website (www.idx.co.id). The population of this study consisted of 13 companies and the sampling method was carried out by purposive sampling method. With this method, a sample of 9 companies was obtained with a 5-year observation method. So the number of observations for this study was 45 observations. To analyze the effect of account receivable turnover, debt to asset ratio, dividend pay-out ratio on profit growth, multiple linear analysis is used with classical assumption test. The results of this study indicate that the account receivable turnover has a positive effect on profit growth, the debt to asset ratio has a negative effect on profit growth, and the dividend pay-out ratio has a positive effect on profit growth.